Woman's Right To Get Freedom In Joseph Ruben's Sleeping With The Enemy Movie (1991): A Feminist Approach - Handayani, Resmi (2012)
The major problem of this research is to explain woman's right to get freedom reflected in Joseph Ruben's Sleeping with the Enemy movie. Objectives of this research are: to analyze the movie based on its structural elements, and to analyze movie based on A Feminist Approach theory by Lady Mary Worley Montagu and The Marquis de Condorcet. In conducting this research, the researcher uses qualitative research, in which the primary data are taken from Sleeping with the Enemy movie and the secondary data are taken from other data related to the research such as movie script, internet and other relevant information. This research comes to the following conclusions. First, based on the structural analysis of the movie, it shows that the character and characterization, setting, plot, point of view, theme, Mise-en-scene, cinematography, sound, and editing are related to each other and form the unity into good quality of a movie. Second, based on Feminist Approach analysis, there are women's position, women's role, women's right, and women's participation. The struggles are getting freedom in women's position as a woman, woman's role in the household, woman's right in her life as a wife.